Sosialisasi Personal Branding sebagai Strategi Pembentukan Identitas Positif Generasi Z Pada Lingkungan SMA Negeri 4 Siak Hulu - Saddam Muhdi; May Valzon; Mukhammad Fathkhur Rozaq; Amelia Elvarani; Arzi Putra Persada; Dinda Lestari; Dheana Salsabiela Eddya; Laila Indah Fitriya; Muga Hapdy Daulay; Prista Indria Nawang Wulan; Raja Alya Zahra; Ummi Azizah Nasution; Widya Ade Putri Sinaga (Karawo : Journal of Community Service (KJCS), 2025)
This community service activity through the Real Work Lecture (KKN) program aims to increase students' understanding and awareness of the importance of personal branding as a strategy for forming a positive identity for Generation Z. The socialization was held on August 28, 2025, at SMA Negeri 4 Siak Hulu, Teratak Buluh Village, targeting 12th grade students. The methods used were face-to-face counseling through PowerPoint presentations, interactive discussions, and evaluations in the form of pre-tests and post-tests to measure the level of understanding before and after the material was delivered. The results of the activity showed a significant increase in the average student understanding score, from 14.70 on the pre-test to 22.55 on the post-test, with a difference of 7.85 points. A paired t-test also showed a significant difference (p < 0.001), confirming that personal branding socialization is effective in improving student understanding. Thus, this activity not only adds to students' knowledge but also provides them with practical skills in building a positive self-identity, increasing their self-confidence, and preparing them to face the challenges of education and work in the digital age.